"You Can Be Creative Once You Are Tenured": Counterstories of Academic Writing From Mid-Career Women Faculty of Color. (3rd July 2022) - Covarrubias, Rebecca; Newton, Xiaoxia; Glass, Tehia Starker
Abstract : Academic writing is a critical activity through which scholars establish their stature in the field with ensuing academic successes. These "successes" rely on conventions that determine what questions are important to ask, what is the most rigorous methodology to employ, what constitutes "good" quality writing, and who is our most important audience. We offer counterstories of how we, three mid-career women faculty of color, navigated conventions of academic writing. We unpack how some conventions limit rather than empower us to exercise our creativity and to claim writing for ourselves and for our communities. We employ counter-storytelling to document a collective reality and to reimagine what constitutes "good" academic writing. Our stories range from challenging dominant and mainstream norms of evaluation and research, to learning to find one's voice in writing, to navigating racist feedback in the peer-review process. Synthesizing across our cases, we conclude with recommendations for reimagining research communication.